Effects of ultrasonic peening treatment on hydrogen sulphide corrosion behaviour. (2nd September 2017) - Feng, Y.; Hu, S.; Wang, D.; Liu, J.; Zhang, C.
ABSTRACT: After being subjected to ultrasonic peening treatment (UPT), the resistance of X65 pipeline steel to hydrogen sulphide corrosion was investigated through electrochemical, immersion and slow-strain-rate testing. In addition, the UPT-induced compressive residual stresses layer and related changes in the steel near-surface microstructure and hardness were examined by scanning electron microscopy, optical microscopy and X-ray diffraction. The obtained results revealed that UPT was able to significantly improve the corrosion potential of X65 pipeline steel and reduce its hydrogen sulphide corrosion rate, while the formation of the compressive stress layer increased the steel's tensile strength and inhibited hydrogen blistering.